NEW METHODS OF TEACHING FOREIGN LANGUAGES AND ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN A DIGITAL EDUCATIONAL ENVIRONMENT - Raxmonova E’zoza (International Journal of Literature and Language Studies, 2026)
This article provides information about the importance of innovative methods based on digital technologies and artificial intelligence in teaching foreign languages, their advantages, methods of application, and their role in the educational process.